PENEREPAN MEDIA PUZZLE UNTUK MENINGKATKAN PEMAHAMAN KONSEP MATEMATIS SISWA KELAS IV PADA MATERI BANGUN DATAR - Herfiana Putri Assakhiy; Delfi Novelia Pratiwi; Diana Ermawati (Universitas Muhammadiyah Semarang, 2024)
The aim of this research is that the application of knowing that puzzle media can improve the understanding of fourth grade students' mathematical concepts related to plane material at SD Negeri 1 Mayongkidul, Mayong District, Jepara Regency, Academic Year 2023/2024. The type of research applied is Classroom Action Research. The subjects of this research were 28 grade IV students at SD Negeri 1 Mayongkidul, including 20 male students and 8 female students. This research consists of two cycles, each cycle consisting of four stages, namely planning, implementing actions, observing and reflecting. Data collection techniques are interviews, observation, tests and documentation. The data analysis used in this research is quantitative and qualitative data analysis. The results of this research show that through the application of puzzle media, fourth grade students at SD Negeri 1 Mayongkidul can improve their understanding of mathematical concepts in flat shape material. This can be seen from the number of students who completed cycle I as many as 16 students with a percentage of 57% (medium category) and the number of students who completed cycle II as many as 23 students with a percentage of 82% (high category). The application of this puzzle media can increase students' understanding of mathematical concepts by fulfilling success indicators.